2009
DOI: 10.5432/ijshs.ijshs20090015
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Judgment of Tennis Serve: A Comparison between Video Images and Computer Graphics Animations

Abstract: This study aimed to explore the feasibility of using computer graphics (CG) animations to evaluate perceptual skills in tennis. In Experiment 1, we used video images or CG animations to examine the visual search behaviors and the accuracy of anticipating serve direction of 18 skilled tennis players. Participants viewed the racket area for a longer time during the 150 ms period immediately before the moment of racket-ball contact in the video image condition opposed to the CG animation condition. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Recently, the effect of using a digital human model for studying the anticipatory performance of a tennis serve was discussed, and a CG display was found to be more similar to a video display rather than to a PLD (Fukuhara et al, 2009). The assessment of a CG display of the manipulated motion in comparison with real world or film remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the effect of using a digital human model for studying the anticipatory performance of a tennis serve was discussed, and a CG display was found to be more similar to a video display rather than to a PLD (Fukuhara et al, 2009). The assessment of a CG display of the manipulated motion in comparison with real world or film remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…The racket model was made of a rigid body polygon. A scripting language (Maya Embedded Language, MEL) was used to convert the motion data to the CG human model (Fukuhara, Ida, Kusubori, & Ishii, 2009). The ball was erased from the animation to eliminate unexpected perceptual effects other than human motion; for example, the racket might miss the ball because the modulation procedure changed the path of the racket.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that CG humans could evoke strong brain activity in the superior temporal sulcus, which is involved in the perception of biological motion [21], [22]. Although the response accuracy decreased when viewing CG displays in comparison with video displays, skilled tennis players could pick up anticipatory cues for the direction of the ball from CG animations of the serve motion [23]. The use of a digital human model allows the easily manipulation of the displayed motions on demand, e.g., the contour, texture, and even the motion itself.…”
Section: Introductionmentioning
confidence: 99%
“…We adopted computer graphic (CG) animations as visual stimuli to accurately evaluate recognition errors between the VAS scores and the original coordinate position output from motion capture data. We used CG animations of forehand shots to test the evaluation validity for anticipatory judgment of shot direction ( Fukuhara et al, 2009 ; Fukuhara et al, 2017 ). First, forehand stroke shots by a professional tennis player (22 years old, 11 years of tennis experience, and ranked in the top 30 in Japan) were recorded on the tennis court using three-dimensional motion capture cameras (Hawk system, Motion Analysis Inc.).…”
Section: Methodsmentioning
confidence: 99%